IVIg-mediated amelioration of ITP in mice is dependent on sialic acid and SIGNR1 - Schwab, Inessa; Biburger, Markus; Krönke, Gerhard; Schett, Georg; Nimmerjahn, Falk (European Journal of Immunology, 2012)
Intravenous immunoglobulin G (IVIg) therapy is widely used to treat autoimmune and inflammatory diseases. Recent evidence suggests that in mice, splenic resident cells might be important for the anti-inflammatory activity of IVIg in a model of serum transfer arthritis. Splenectomized human immunothrombocytopenia (ITP) patients, however, still respond to IVIg therapy. To investigate whether the requirement of the spleen is essential for mouse ITP, we used a passive model of induced ITP and demonstrated that IVIg activity was functional in splenectomized animals. Further analysis showed that the IVIg-mediated amelioration of platelet phagocytosis was fully dependent on terminal sialic acid residues in the IVIg preparation and could be blocked with a specific ICAM3 grabbing nonintegrin-related 1 (SIGNR1) specific antibody. These results suggest that, similar to the human system, a spleen-independent but sialic acid- and SIGNR1-dependent pathway is responsible for IVIg-mediated suppression of autoantibody-dependent platelet depletion in mice. © 2012 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
Keywords: Fc-receptor · ITP · IVIg · Sialic acid · SIGNR1